Integrating Green Marketing and Environmental Behavior to Predict Revisit Intention in Indonesian Ecotourism - Andina Fasha; Cheryn Kang; Lady Lady; Budi Setiawan (Penerbit Goodwood, 2026)
Purpose: The escalation of ecotourism as sustainability-oriented travel highlights the inconsistency of tourists' responsible actions during visits, which is also known as the attitude-behavior gap, whereas environmental concern does not necessarily translate into action, as discussed in sustainable tourism literature. Research Methodology: A quantitative approach was employed using Partial Least Squares Structural Equation Modeling, collected through questionnaire surveys from 478 tourists who had previously visited Ecotourism destinations in Batam City, Indonesia, using SmartPLS 4. Results: The findings show how direct environmental experiences at the destination were more effective in encouraging responsible tourist behavior than pre-visit digital exposure, which presumes that it is more likely to develop revisit intentions as long-term destination loyalty. Conclusions: The study highlights the importance of environmental behavior in fostering revisit intention within ecotourism destinations and suggests that direct interpretive experiences at the destination may play a more influential role in shaping tourists’ behavior than digital promotional exposure alone. Limitations: This study was limited to one ecotourism site in Batam City, with cross-sectional self-reported data, which may have limited generalizability. Contributions: This study extends sustainable tourism literature by integrating digital green marketing, environmental belief, and environmental interpretation into a unified behavioral framework explaining revisit intention through environmental behavior and offer practical insights for ecotourism managers to strengthen sustainable behavior and long-term destination loyalty through effective communication and interpretation strategies